Comparative Analysis of JSA (Job Safety Analysis) of Smoked Fish MSMEs SAD Community and the General Public - Hasanuddin Hasanuddin; Rd. Halim; Ummi Kalsum; Dwi Noerjoedianto; M. Ridwan (CV. AFDIFAL MAJU BERKAH, 2025)
This study aims to analyze occupational safety in the smoked fish production process through the Job Safety Analysis (JSA) approach in two groups of micro, small, and medium business actors, namely those managed by the Suku Anak Dalam community and those managed by the general public. The research method used is descriptive qualitative with a field observation approach and in-depth interviews to identify potential hazards and preventive measures taken at each stage of work. The results of the study indicate that in business units managed by the Suku Anak Dalam community, most work stages have the potential to cause hazards, but are not accompanied by adequate preventive measures. In contrast, in business units of the general public, several basic control measures have been implemented, such as the use of aids, gloves, masks, and protective shoes. This difference indicates a gap in the implementation of occupational safety due to factors of knowledge, culture, and access to information. This study concludes that a culture-based and educational occupational safety approach is needed to increase awareness and prevent work accidents, especially in remote indigenous communities